Feminist lives women, feelings, and the self in post-war Britain - Abrams, Lynn 1960- (Oxford scholarship online, 2023)
This work tells the story of women growing up in post-war Britain, rejecting the self-sacrifice of their mothers' generation and embracing new ways of living, feeling, and being in the decades before Women's Liberation. They were feminists before feminism, which we see through their descriptions of themselves, their relationships, their feelings, and actions